Performance of fractional-order control of cooperative robots - Ferreira, N. M Fonseca (2019)
In this paper it is studied the implementation of fractional-order algorithms in the position/force control of two cooperating robotic manipulators. The system performance is analyzed in the time and frequency domains. The effect of backlash and flexibility at the robot joints is also investigated.